Novel Rheumatoid Arthritis Susceptibility Locus at 22q12 Identified in an Extended UK Genome‐Wide Association Study. Issue 1 (January 2014) - Orozco, Gisela; Viatte, Sebastien; Bowes, John; Martin, Paul; Wilson, Anthony G.; Morgan, Ann W.; Steer, Sophia; Wordsworth, Paul; Hocking, Lynne J.; UK Rheumatoid Arthritis Genetics Consortium; Wellcome Trust Case Control Consortium; Biologics in Rheumatoid Arthritis Genetics and Genomics Study Syndicate Consortium; et al.
<x xml:space="preserve">Abstract</x> Objective The number of confirmed rheumatoid arthritis (RA) loci currently stands at 32, but many lines of evidence indicate that expansion of existing genome‐wide association studies (GWAS) enhances the power to detect additional loci. This study was undertaken to extend our previous RA GWAS in a UK cohort, adding more independent RA cases and healthy controls, with the aim of detecting novel association signals for susceptibility to RA in a homogeneous UK cohort. Methods A total of 3, 223 UK RA cases and 5, 272 UK controls were available for association analyses, with the extension adding 1, 361 cases and 2, 334 controls to the original GWAS data set. The genotype data for all RA cases were imputed using the Impute program version 2. After stringent quality control thresholds were applied, 3, 034 cases and 5, 271 controls (1, 831, 729 single‐nucleotide polymorphisms [SNPs]) were available for analysis. Association testing was performed using Plink software. Results The analyses indicated a suggestive association with susceptibility to RA (P < 0.0001) for 6 novel RA loci that have been previously found to be associated with other autoimmune diseases; these 6 SNPs were genotyped in independent samples. Two of the associated loci were validated, one of which was associated with RA at genome‐wide levels of significance in the combined analysis, identifying a novel RA locus at 22q12 (P = 6.9 × 10−9). In addition, most of the previously known RA susceptibility loci were confirmed to be associated with RA, and for 16 of the loci, the strength of the association was increased. Conclusion This study identified a new RA locus mapping to 22q12. These results support the notion that increasing the power of GWAS enhances novel gene discovery.